Microglial- neuronal crosstalk in chronic viral infection through mTOR, SPP1/OPN and inflammasome pathway signaling - Argandona Lopez, Catalina; Brown, Amanda M. (Frontiers in Immunology, 2024)
HIV-infection of microglia and macrophages (MMs) induces neuronal injury and chronic release of inflammatory stimuli through direct and indirect molecular pathways. A large percentage of people with HIV-associated neurologic and psychiatric co-morbidities have high levels of circulating inflammatory molecules. Microglia, given their susceptibility to HIV infection and long-lived nature, are reservoirs for persistent infection. MMs and neurons possess the molecular machinery to detect pathogen nucleic acids and proteins to activate innate immune signals. Full activation of inflammasome assembly and expression of IL-1b requires a priming event and a second signal. Many studies have demonstrated that HIV infection alone can activate inflammasome activity. Interestingly, secreted phosphoprotein-1 (SPP1/OPN) expression is highly upregulated in the CNS of people infected with HIV and neurologic dysfunction. Interestingly, all evidence thus far suggests a protective function of SPP1 signaling through mammalian target of rapamycin (mTORC1/2) pathway function to counter HIV-neuronal injury. Moreover, HIV-infected mice knocked down for SPP1 show by neuroimaging, increased neuroinflammation compared to controls. This suggests that SPP1 uses unique regulatory mechanisms to control the level of inflammatory signaling. In this mini review, we discuss the known and yet-to-be discovered biological links between SPP1-mediated stimulation of mTOR and inflammasome activity. Additional new mechanistic insights from studies in relevant experimental models will provide a greater understanding of crosstalk between microglia and neurons in the regulation of CNS homeostasis.